(untitled) (World Science, 2019)
The article presents the results of a study of the paths for the career development of pharmacists who have studied at Kyiv Medical University, Kyiv (KMU), in terms of activities, occupations and options for their further professional training, as well as the impact of the various disciplines chosen for study by students on their further career development. It is shown that the development of optional training courses for students focused on how they can make more efficient career choices will help their long term career development.